Innovation in banana value chain development in Metema district, northwestern Ethiopia: IPMS experiences - Berhe, Kahsay; Puskur, Ranjitha; Teka, W.; Hoekstra, Dirk; Tegegne, Azage (International Livestock Research Institute, 2008)
Ethiopia has a diverse agro-ecology and sufficient surface and ground water resources, suitable for growing various temperate and tropical fruits. Although various tropical and temperate fruits are grown in the lowland/midland and highland agro-ecologies, the area coverage is very limited. For example, banana export increased from less than 5,000 tons in 1961 to 60,000 tons in 1972, but in 2003 declined to about 1,300 tons worth less than USD 350,000. The limited development of fruit sector in the country could be attributed to constraints such as limited inputs, skilled manpower and extension approaches and, focus of agricultural development efforts on grain production amongst others. The current government’s policy and development strategy prioritizes intensive production and commercialization of agriculture, including fruit production. In an effort to support this change, the International Livestock Research Institute (ILRI) and the Ministry of Agriculture and Rural Development (MoARD) initiated a five-year project with financial assistance from Canada, called improving productivity and market success (IPMS) of Ethiopian farmers. IPMS follows participatory value chain and innovation systems perspectives and focuses on knowledge-based development of identified agricultural commodities with market potential in 10 pilot learning weredas (districts) in four regional states. One of the weredas is Metema where the project introduced banana production. The objective of this paper is to share IPMS experiences in promoting innovation in banana value chain development in Metema wereda. The paper provides a brief history of banana introduction in Ethiopia, describes the value chain in banana production, input supply and marketing and the various innovations that have been introduced to develop the chain, with a focus on actors and action learning processes. The future outlooks of banana value chain and the reasons for the successful adoption of the innovation and the options to sustain it so that the value chain can respond to changing conditions are highlighted.